Patient Activation in Acute Decompensated Heart Failure - Dunlay, Shannon M. (J Cardiovasc Nurs, 2017)
BACKGROUND: Recent data suggest that patient activation, or having the knowledge, skills and confidence to engage and manage one's own health, favorably impacts patient behaviors and health outcomes. However, the role of activation in patients with heart failure is unknown. OBJECTIVES: To measure the level of activation of patients hospitalized with acute decompensated heart failure (ADHF) and to determine whether activation is associated with in-hospital and early post-discharge outcomes. METHODS: We prospectively recruited Southeastern Minnesota residents hospitalized at Mayo Clinic hospitals with ADHF from January 2014- July 2015. Activation was measured using the Patient Activation Measure questionnaire. RESULTS: Among the 302 patients enrolled, the mean age was 77.3 years, 57.3% were men, and 46.8% had preserved ejection fraction. The median (25th-75th percentile) length of stay was 4 (3-7) days. In total, 7 (2.3%) patients died prior to discharge. Most survivors discharged to home (73.6%) or skilled nursing facilities (23.7%). The number (%) of patients in each activation level from highest to lowest was 9 (3.0%), 121 (40.1%), 122 (40.4%), and 50 (16.6%). Patients with lower activation were older, less educated, had lower patient satisfaction, and worse health literacy. They more often discharged to skilled nursing facilities and had higher 30-day mortality, though 30-day readmission did not differ by activation. CONCLUSIONS: Patients hospitalized with ADHF with lower activation are less satisfied, have worse health literacy, more often require skilled care and are at increased risk for early post-discharge mortality. Activation can be easily measured and may help clinicians identify high-risk patients.